2019
DOI: 10.1101/702357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult crowding induces sexual dimorphism in chronic stress-response inDrosophila melanogaster

Abstract: disorders 19 SUMMARY STATEMENT 20 Female fruit flies, like their human counterparts, are more prone to chronic stress-induced 21 mood disorders like anhedonia or reduced activity. This sexual dimorphism was more evident 22 in a biotic stress. 23ABSTRACT 24 Stress-induced mood disorders such as depression and anxiety are sexually dimorphic in 25 human beings. Studying behavioural stress-responses in non-human animal models can help 26 better understand the behavioural manifestations of these disorders and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(94 reference statements)
1
0
0
Order By: Relevance
“…Similar behaviour was shown by males of the tropical butterfly Bicyclus anynana, which exhibited the higher mobility than female butterflies (Reim et al, 2019). A previous study also revealed a sexually dimorphic response to stress (mechanical perturbation and adult crowding) in Drosophila females, which exhibited reduced motivation towards the exploration of novel habitats (Lall et al, 2019). Similarly, dspfk-injected male dealates spent more time and covered a significantly greater distance in the wall zone in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Similar behaviour was shown by males of the tropical butterfly Bicyclus anynana, which exhibited the higher mobility than female butterflies (Reim et al, 2019). A previous study also revealed a sexually dimorphic response to stress (mechanical perturbation and adult crowding) in Drosophila females, which exhibited reduced motivation towards the exploration of novel habitats (Lall et al, 2019). Similarly, dspfk-injected male dealates spent more time and covered a significantly greater distance in the wall zone in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Keuntungan lain bila menggunakan Drosophila, yaitu siklus hidupnya yang pendek sekitar 12 hari, akan memudahkan untuk menganalisis pengaruh dari penggunaan suatu zat atau senyawa yang berhubungan dengan stres (Ibrahim et al, 2018). Menurut para ahli, Drosophila memiliki stuktur dan fungsi seluler dasar yang mirip dengan manusia sehingga memudahkan untuk mempelajari kelulusan hidup dan gerak lokomotornya pada saat terpapar zat penyebab stres (Lall et al, 2019).…”
Section: Pendahuluanunclassified